The Influence of Waste of Pineapple’s Peel (Ananas Comosus (L) Merr) As The Source of Bromelain Enzyme to Increase Meat (Local Beef) Quality - Nur Alawiyah; Ratih Rizqi Nirwana; Siti Tarwiyah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2015)
The subjects of this research are waste of pinepple’s peel (Ananas Comosus (L) Merr) and local beef that were obtained from Jrakah traditional market, Ngaliyan-Semarang. The data technique analysis of this research is descriptive statistics. The result of this research shows that there is influence of waste of pineapple’s peel as source of bromelain enzyme to increase meat quality, especially tenderness. The higher the bromelain enzyme concentration used, the more tender the meat, although will be may increase the score of cooking loss. The meat that is submerged with the highest concentration (40%) of bromelain enzyme solution has score of 0.6662 and 45% of cooking loss. The organoleptic quality identification of meat that is submerged with bromelain enzyme solution, generally is better than the control meat. The meat that is submerged with bromelain enzyme solution gives better appearance, flavor, juiceness, and tenderness than the control meat. © 2015 JNSMR UIN Walisongo. All rights reserved.